Positive electrode active material and preparation method thereof, positive plate and battery
By covering the cladding of CeO2 and fast ion conductors on the surface of single-crystalline lithium manganate material, the problems of deterioration of cycle performance and structural damage of lithium manganate batteries are solved, and better battery performance and rate performance are achieved.
Patent Information
- Application Number
- CN202411720336.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-11-28
AI Technical Summary
Lithium manganate batteries are prone to side reactions with the electrolyte during circulation, resulting in deterioration of circulation performance. During the positive electrode preparation process, rolling pressure will destroy the structure of single-crystal lithium manganate, affecting battery performance.
The surface of the single-crystal lithium manganate material is coated with a cladding layer including CeO2 and fast ion conductor, effectively isolating the contact between the electrolyte and the lithium manganate material and improving the lithium ion transmission rate.
Improve the cycling performance of the battery, prevent the roller from destroying the material structure, improve the rate performance and reduce the internal resistance of the battery.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium battery production, and in particular to a positive electrode active material and a preparation method thereof, a positive electrode sheet and a battery. Background Art
[0002] Compared with other rechargeable battery systems, lithium-ion secondary batteries have the advantages of high operating voltage, light weight, small size, no memory effect, low self-discharge rate, long cycle life, and high energy density. They are currently widely used in mobile phones, laptops, tablet computers, electric vehicles, energy storage grids, etc. In recent years, with the rapid development of electric vehicles, people have higher demands for battery energy density, safety, cost and environmental protection.
[0003] Lithium manganese oxide has attracted wide attention due to its abundant resources and low price. However, there are a large number of trivalent manganese ions in lithium manganese oxide, which are prone to side reactions with the electrolyte, causing the battery's cycle performance to deteriorate. The battery prepared with single-crystal lithium manganese oxide has good cycle performance, but low capacity. Polycrystalline lithium manganese oxide has high capacity, but poor battery cycle performance. Single-crystal lithium manganese oxide has a unique microstructure with dense agglomeration, small particle gaps, and smooth surface, which can effectively reduce the exposed area of the material and contact with the electrolyte. In order to further improve the battery's cycle performance and prevent the single-crystal structure of lithium manganese oxide from being destroyed by rolling when preparing the positive electrode, the single-crystal lithium manganese oxide is coated. The coating layer in the existing technology has poor lithium ion transmission, which makes the advantage of the fast diffusion of single-crystal lithium manganese oxide unable to be manifested, and the coating will increase the internal resistance of the battery. Summary of the invention
[0004] In order to solve the above technical problems, the present invention discloses a positive electrode active material and a preparation method thereof, a positive electrode sheet, and a battery. The present invention can effectively isolate the contact between the electrolyte and the lithium manganese oxide material by coating the surface of the lithium manganese oxide with a coating layer including CeO2 and a fast ion conductor, thereby effectively improving the cycle performance of the battery.
[0005] The technical solution of the present invention is implemented as follows:
[0006] In a first aspect, the present application provides a positive electrode active material, comprising a single-crystal lithium manganate material, and a coating layer formed on the surface of the single-crystal lithium manganate material, wherein the coating layer comprises CeO2 and a fast ion conductor;
[0007] The general formula of the single-crystal lithium manganate material is Li 1+a Mn 2-a-b-c B b M c O4, wherein 0.001≤a≤0.30, 0.001≤b≤0.2, 0.001≤c≤0.2, and M is a metal element.
[0008] In one embodiment, the fast ion conductor is LiNbO3, Li4Ti5O 12 , at least one of Li2TiO3, LiAlO2, LiTaO3, LiMoO3, Li2RuO3 or Li2WO4.
[0009] In one embodiment, M includes at least two of Mg, Al, Ca, Ti, Cu, Zn, Y, Zr, Nb, Mo, Ru, Sn, and Sb.
[0010] In a preferred embodiment, the M includes at least two of Al, Mg, Ti, Co, and Nb.
[0011] In one embodiment, the thickness of the coating layer is 10 nm to 50 nm.
[0012] In one embodiment, based on 100% of the mass of the positive electrode active material, the mass of the fast ion conductor material accounts for 0.1% to 2%.
[0013] In one embodiment, based on the mass of the positive electrode active material being 100%, the mass of CeO 2 accounts for 0.1% to 2%.
[0014] In one embodiment, the mass ratio of CeO 2 to the fast ion conductor is (4:6) to (7:3).
[0015] In one embodiment, the particle size ratio of CeO 2 to the fast ion conductor is (1-1.5):1.
[0016] The second aspect of the present invention is to propose a method for preparing a positive electrode active material, which is used to prepare the positive electrode active material disclosed in the first aspect of the present invention. The method comprises the following steps:
[0017] S1, uniformly mixing a spherical or quasi-spherical Mn-containing precursor, a lithium source, a B source and an M source to form a first mixture;
[0018] S2, calcining the first mixture in an air atmosphere to obtain a single-crystal lithium manganate material;
[0019] S3, weighing the quasi-single-crystal lithium manganate material obtained in step S2, adding a solvent, and stirring evenly to form a first solution;
[0020] S4, adding CeO2 material and fast ion conductor material to the first solution prepared in step S3, and continuing to stir until a suspension is formed;
[0021] S5, dry;
[0022] S6, calcining the dried powder obtained in step S5 under air atmosphere to obtain a positive electrode active material;
[0023] Wherein, the particle size of the Mn-containing precursor is 1 μm to 5 μm;
[0024] In the step S2, the calcination temperature is 600°C to 880°C;
[0025] In one embodiment, the Mn-containing precursor includes manganese tetraoxide, manganese trioxide, or manganese carbonate, or a mixture of the two.
[0026] In one embodiment, the lithium source is one or both of lithium carbonate and lithium hydroxide.
[0027] In one embodiment, the M source is an oxide or sulfate of a metal element M; the metal element M includes at least two of Mg, Al, Ca, Ti, Cu, Zn, Y, Zr, Nb, Mo, Ru, Sn, and Sb.
[0028] In one embodiment, the metal element M includes at least two of Al, Mg, Ti, Co, and Nb.
[0029] In one embodiment, in step S2, the calcination time is 5 hours to 24 hours.
[0030] In one embodiment, in step S2, the calcination time is 8 hours to 20 hours.
[0031] In a specific application, in addition to selecting the endpoints of 8h and 20h, any value in the above range may also be selected, such as 10h, 12h, 15h, 18h, etc. The present invention does not impose any limitation on this.
[0032] In one embodiment, in step S2, stirring is continued at 40° C.-60° C. for 2 h-8 h to obtain a suspension of the three mixtures.
[0033] In one embodiment, in step S6, the dry powder obtained in step S5 is calcined at 400° C.-600° C. for 6 h-15 h in an air atmosphere to obtain a positive electrode active material.
[0034] The third aspect of the present invention is to provide a positive electrode sheet, which includes a positive electrode active material provided in the first aspect of the present invention, a conductive agent and a binder.
[0035] The fourth aspect of the present invention is to provide a battery, which includes the positive electrode sheet, the negative electrode sheet, the separator, and the electrolyte provided in the third aspect of the present invention.
[0036] The advantages of the present invention are as follows:
[0037] By coating the surface of the single-crystal lithium manganate material with a coating layer including CeO2 and a fast ion conductor, the contact between the electrolyte and the lithium manganate material can be effectively isolated, the cycle performance of the battery can be improved, and the damage to the single-crystal lithium manganate material by rolling can be effectively prevented. In addition, the synergistic effect of CeO2 and the fast ion conductor can effectively improve the lithium ion transmission rate of the coating layer, which is conducive to the preparation of a thin coating layer with good insulation effect, thereby effectively giving play to the advantages of the single-crystal lithium manganate material, improving the rate performance of the battery prepared therefrom, and reducing the internal resistance of the battery.
[0038] Furthermore, the lithium manganese oxide material is co-doped with B and at least two metal elements. The B element doping can effectively reduce the melting temperature of the raw materials during sintering, which is beneficial to the formation of a single-crystal structure and to improve the lattice stability of the single-crystal lithium manganese oxide material, thereby further improving the cycle performance of the battery prepared therefrom. DETAILED DESCRIPTION
[0039] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0040] Unless otherwise defined, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by technicians in the technical field to which the present invention belongs; the terms used in the specific implementation methods are only for the purpose of describing specific embodiments and are not intended to limit the present invention; the terms "including" and "having" in the description and claims of the present invention and any variations thereof are intended to cover non-exclusive inclusions.
[0041] In the description of the specific implementation methods of the present invention, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present invention, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.
[0042] Reference to "embodiments" in the present invention means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present invention. The appearance of the phrase in various places in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described in the present invention may be combined with other embodiments.
[0043] In the description of the embodiments of the present invention, the term "and / or" is only a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in the present invention generally indicates that the associated objects before and after are in an "or" relationship.
[0044] Throughout the present invention, numerical values represent approximate measures or limits of ranges to cover minor deviations from given values as well as embodiments with about the values mentioned and embodiments with the exact values mentioned. Except for the working examples provided at the end of the detailed description, all numerical values of parameters (e.g., amounts or conditions) in this specification (including the appended claims) should be understood to be modified by the term "about" in all cases, regardless of whether "about" actually appears before the numerical value. "About" indicates that the stated numerical value allows some minor imprecision (close to the exact value of the value to some extent; approximately or reasonably close to the value; almost). If the imprecision provided by "about" is not otherwise understood in this ordinary sense in the art, "about" as used in the present invention at least indicates the variation that can be produced by the ordinary methods of measuring and using such parameters. For example, "about" may include a variation of less than or equal to 5%, optionally less than or equal to 4%, optionally less than or equal to 3%, optionally less than or equal to 2%, optionally less than or equal to 1%, optionally less than or equal to 0.5%, and in some aspects, optionally less than or equal to 0.1%.
[0045] Additionally, disclosure of ranges includes disclosure of all values within the entire range and further divided ranges, including endpoints and sub-ranges given for such ranges.
[0046] On the one hand, lithium manganese oxide materials contain trivalent manganese ions. During the charge and discharge process, lithium manganese oxide materials will react with the electrolyte, causing the trivalent manganese ions in lithium manganese oxide to undergo a disproportionation reaction to generate divalent manganese ions. The divalent manganese ions migrate to the negative electrode side for reduction, which will destroy the SEI film on the negative electrode side, causing the SEI film on the negative electrode side to be continuously destroyed and regenerated, consuming lithium ions, thereby causing the battery's cycle performance to deteriorate. On the other hand, affected by the Chiang-Taylor effect, lithium manganese oxide materials are prone to crystal structure changes during the charge and discharge process, affecting their cycle stability.
[0047] The single-crystal lithium manganese oxide has a unique microstructure with dense agglomeration, small particle gap and smooth surface, which can effectively reduce the exposed area of the material and the contact with the electrolyte, thereby slowing down the Mn 3+ However, in the process of preparing the positive electrode of the battery, in order to adjust the thickness and compaction density of the positive electrode sheet, the positive electrode sheet needs to be rolled, and a large pressure will destroy the structure of the single-crystal lithium manganese oxide.
[0048] In order to further improve the cycle performance of the battery and prevent the single crystal structure of lithium manganese oxide from being destroyed by rolling when preparing the positive electrode, the single crystal lithium manganese oxide is coated. The lithium ion transmission of the coating layer in the existing technology is poor, resulting in the advantage of fast diffusion of single crystal lithium manganese oxide ions cannot be manifested, and the coating will cause the internal resistance of the battery to increase.
[0049] In order to solve the above technical problems, the present invention discloses a positive electrode active material and a preparation method thereof, a positive electrode sheet, and a battery. The present invention can effectively isolate the contact between the electrolyte and the lithium manganese oxide material by coating a coating layer including CeO2 and a fast ion conductor on the surface of the single-crystal lithium manganese oxide material, thereby effectively improving the cycle performance of the battery.
[0050] The technical solution of the present invention is implemented as follows:
[0051] In a first aspect, the present application provides a positive electrode active material, comprising a single-crystal lithium manganate material, and a coating layer formed on the surface of the single-crystal lithium manganate material, wherein the coating layer comprises CeO2 and a fast ion conductor;
[0052] The single-crystal lithium manganate material has a general formula of Li 1+a Mn 2-a-b-c B b M c O4, where 0.001≤a≤0.30, 0.001≤b≤0.2, 0.001≤c≤0.2;
[0053] M is a metal element.
[0054] On the one hand, CeO2 has good electron conductivity, and fast ion conductors have good ion conductivity, but poor electronic conductivity. The synergistic effect of the two is conducive to improving the lithium ion transmission capacity of the coating layer, thereby improving the rate performance of the battery prepared therefrom and reducing the internal resistance of the battery. On the other hand, when CeO2 is used as a coating material, lithium ions diffuse vertically and the transmission path is shorter, which is conducive to the rapid transmission of lithium ions. Combined with the lithium ion transmission of fast ion conductors, it is conducive to further improving the ion conduction capacity of the combination of CeO2 and fast ion conductors.
[0055] In addition, when CeO2 is used as a coating material, it is conducive to forming a dense coating layer, which is conducive to further enhancing the isolation effect on the electrolyte and the positive electrode active material. Moreover, based on the good lithium ion transmission effect of the coating layer, the formation of a dense coating will not affect the performance of the battery.
[0056] Furthermore, the lithium manganese oxide material is co-doped with B and metal elements. The B element doping can effectively reduce the melting temperature of the raw materials during sintering, which is beneficial to the formation of a single crystal structure and to improve the lattice stability of the single crystal lithium manganese oxide material, thereby further improving the cycle performance of the battery prepared therefrom.
[0057] In one embodiment, the fast ion conductor is LiNbO3, Li4Ti5O 12 , at least one of Li2TiO3, LiAlO2, LiTaO3, LiMoO3, Li2RuO3 or Li2WO4.
[0058] The term "at least one" as used in the present invention refers to selecting one of the listed materials, or selecting a mixture of two or more materials. Those skilled in the art can freely select the material within the scope of their understanding. The present invention does not impose any limitation on this.
[0059] In one embodiment, M includes at least two of Mg, Al, Ca, Ti, Cu, Zn, Y, Zr, Nb, Mo, Ru, Sn, and Sb.
[0060] The term "at least two" as used in the present invention refers to selecting any two or more materials from the above-mentioned materials for mixing. Those skilled in the art may freely select the materials within the scope of their understanding. The present invention does not impose any limitation on this.
[0061] In one embodiment, M includes at least two of Al, Mg, Ti, Co, and Nb.
[0062] Metal elements can form chemical bonds with O, which is beneficial to improving the crystal structure stability of lithium manganese oxide materials.
[0063] In one embodiment, the thickness of the coating layer is 10 nm to 50 nm.
[0064] The thickness range of the coating layer disclosed in the present invention means that those skilled in the art can implement the coating layer thickness of the end points of 10nm and 50nm, and can also implement any value in the range, such as 12nm, 15nm, 20nm, 25nm, 30nm, 35nm, 40nm, 45nm, etc. The present invention does not impose any limitation on this.
[0065] In one embodiment, based on 100% of the mass of the positive electrode active material, the mass of the fast ion conductor material accounts for 0.1% to 2%.
[0066] The mass ratio of the fast ion conductor material to the positive electrode active material disclosed in the present invention may be any value in the range except for the endpoints of 0.1% and 2%, such as 0.2%, 0.5%, 0.8%, 1%, 1.2%, 1.5%, 1.8%, etc. The present invention does not impose any limitation on this.
[0067] In one embodiment, based on the mass of the positive electrode active material being 100%, the mass proportion of CeO 2 is 0.1% to 2%.
[0068] The mass ratio of CeO2 to the positive electrode active material disclosed in the present invention may be any value within the range except for the endpoints of 0.1% and 2%, such as 0.2%, 0.5%, 0.8%, 1%, 1.2%, 1.5%, 1.8%, etc. The present invention does not impose any limitation on this.
[0069] In one embodiment, the mass ratio of CeO2 to the fast ion conductor is (4:6) to (7:3). A mass ratio that is too large or too small is not conducive to the coordinated cooperation between CeO2 and the fast ion conductor, and is not conducive to further improving the lithium ion transmission rate in the coating layer. Therefore, the present invention limits the mass ratio of CeO2 to the fast ion conductor to the above range, which is more conducive to the rapid transmission of lithium ions in the coating layer.
[0070] The mass ratio of CeO2 to fast ion conductor disclosed in the present invention can be any value in the range except for the endpoints 4:6 and 7:3, such as 4:5, 4:3, 5:6, 5:5, 5:4, 6:6, 6:4, 7:6, 7:4, etc. The present invention does not impose any limitation on this.
[0071] In one embodiment, the particle size ratio of CeO2 to the fast ion conductor is (1-1.5): 1. The present invention can further enhance the isolation effect on the electrolyte by controlling the particle size ratio of CeO2 to the fast ion conductor.
[0072] The particle size ratio of CeO2 to the fast ion conductor disclosed in the present invention is a range, and in addition to the end points 1:1 and 1.5:1, any value in the range can also be implemented, such as 1.1:1, 1.2:1, 1.3:1, 1.4:1, etc. The present invention does not impose any limitation on this.
[0073] The second aspect of the present invention is to propose a method for preparing a positive electrode active material, which is used to prepare the positive electrode active material disclosed in the first aspect of the present invention. The method comprises the following steps:
[0074] S1, uniformly mixing a spherical or quasi-spherical Mn-containing precursor, a lithium source, a B source and an M source to form a first mixture;
[0075] S2, calcining the first mixture in an air atmosphere to obtain a single-crystal lithium manganate material;
[0076] S3, weighing the quasi-single-crystal lithium manganate material obtained in step S2, adding a solvent, and stirring evenly to form a first solution;
[0077] S4, adding CeO2 material and fast ion conductor material to the first solution prepared in step S3, and continuing to stir until a suspension is formed;
[0078] S5, dry;
[0079] S6, calcining the dried powder obtained in step S5 under air atmosphere to obtain a positive electrode active material;
[0080] Wherein, the particle size of the Mn-containing precursor is 1 μm to 5 μm; the particle size range of the Mn-containing precursor disclosed in the present invention refers to any value between the range except the end points 1 μm and 5 μm that can be implemented. For example, 2 μm, 3 μm, 4 μm, etc. The present invention does not impose any restrictions on this. The Mn-containing precursor has a small particle size and a narrow distribution, which is conducive to the preparation of single-crystal lithium manganate materials.
[0081] In the step S2, the calcination temperature is 600°C to 880°C;
[0082] If the calcination temperature is too high, it is not conducive to the formation of a single crystal-like structure. The present invention sets the calcination temperature within the above range, which can promote the formation of a single crystal-like structure. In specific applications, except for the endpoints of 600°C and 880°C, any value within the above range can be selected. For example, 650°C, 680°C, 700°C, 750°C, 780°C, 800°C, 820°C, 850°C, etc. The present invention does not impose any limitation on this.
[0083] In one embodiment, the Mn-containing precursor includes manganese tetraoxide, manganese trioxide, or manganese carbonate, or a mixture of the two.
[0084] In one embodiment, the lithium source is one or both of lithium carbonate and lithium hydroxide.
[0085] In one embodiment, the amount of the lithium source should be 1-5% more than the theoretical value.
[0086] The present invention increases the amount of lithium source on the basis of the theoretical value, so that the volatilization of lithium element during high-temperature calcination can be supplemented.
[0087] In one embodiment, the M source refers to an oxide or sulfate containing a metal element M; the metal element M includes at least two of Mg, Al, Ca, Ti, Cu, Zn, Y, Zr, Nb, Mo, Ru, Sn, and Sb.
[0088] In one embodiment, the metal element M includes at least two of Al, Mg, Ti, Co, and Nb.
[0089] In one embodiment, in step S2, the calcination time is 5 hours to 24 hours.
[0090] In one embodiment, in step S2, the calcination time is 8 hours to 20 hours.
[0091] In a specific application, in addition to selecting the endpoints of 8h and 20h, any value in the above range may also be selected, such as 10h, 12h, 15h, 18h, etc. The present invention does not impose any limitation on this.
[0092] In one embodiment, in step S2, stirring is continued at 40° C.-60° C. for 2 h-8 h to obtain a suspension of the three mixtures.
[0093] In one embodiment, in step S6, the dry powder obtained in step S5 is calcined at 400° C.-600° C. for 6 h-15 h in an air atmosphere to obtain a positive electrode active material.
[0094] The third aspect of the present invention is to provide a positive electrode sheet, which includes a positive electrode active material provided in the first aspect of the present invention, a conductive agent and a binder.
[0095] The binder improves the bonding of the positive electrode active material particles to each other and also improves the bonding of the positive electrode material layer to the positive electrode current collector.
[0096] In one embodiment, non-limiting examples of binders include polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin, nylon, etc.
[0097] In one embodiment, the mass of the binder accounts for 1%-20% of the mass of the positive electrode material layer.
[0098] Conductive agent, which gives the electrode conductivity.
[0099] In one embodiment, the conductive agent may include any conductive material as long as it does not cause chemical changes. Non-limiting examples of conductive materials include carbon-based materials (e.g., natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, etc.), metal-based materials (e.g., metal powder, metal fiber, etc., including, for example, copper, nickel, aluminum, silver, etc.), conductive polymers (e.g., polyphenylene derivatives), and mixtures thereof.
[0100] In one embodiment, the mass of the conductive agent accounts for 1%-20% of the mass of the positive electrode material layer.
[0101] In one embodiment, the positive electrode plate includes a positive electrode current collector. Exemplarily, the positive electrode current collector may be aluminum (Al), but is not limited thereto.
[0102] The fourth aspect of the present invention is to provide a battery, which includes the positive electrode sheet, the negative electrode sheet, the separator, and the electrolyte provided in the third aspect of the present invention.
[0103] Negative electrode:
[0104] In one embodiment, the negative electrode plate includes a current collector and a negative electrode active material layer disposed on the current collector.
[0105] In the present invention, the specific types of negative electrode active materials are not specifically limited and can be selected according to needs. Specifically, the negative electrode active material is selected from natural graphite, artificial graphite, mesophase microcarbon beads (MCMB for short), hard carbon, soft carbon, silicon, silicon-carbon composite, Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO2, spinel structured lithiated TiO2-Li4Ti5O 12 , Li-Al alloy. Non-limiting examples of carbon materials include crystalline carbon, amorphous carbon and mixtures thereof. Crystalline carbon can be amorphous or flake-shaped, platelet-shaped, spherical or fibrous natural graphite or artificial graphite. Amorphous carbon can be soft carbon, hard carbon, mesophase pitch carbide, calcined coke, etc.
[0106] In one embodiment, metal elements and metal compounds can also be selected as negative electrode active materials, such as compounds containing metals or metalloids such as Li, Ag, Al, Bi, Cu, Ga, Ge, In, Ni, Pb, Sb, Si, Sn, Sr, and Zn.
[0107] In one embodiment, the mass percentage of the negative electrode active material contained in the negative electrode active material layer may be 80%-99%, for example, 80%, 85%, 90%, 95%, 97%, 99%, etc., preferably 95%-97%.
[0108] In one embodiment, the negative electrode material layer may include a binder; the binder improves the bonding between negative electrode active material particles and the bonding between the negative electrode active material and the current collector.
[0109] In one embodiment, non-limiting examples of binders include polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin, nylon, etc.
[0110] In one embodiment, the negative electrode active material layer can be obtained by coating a negative electrode slurry on a negative electrode current collector and then drying the negative electrode slurry. The negative electrode slurry includes at least a negative electrode active material and a negative electrode binder. When an aqueous solvent is used as a liquid medium for forming the negative electrode slurry, a thickener is preferably used for slurrying. The thickener can generally be used to adjust the viscosity of the slurry.
[0111] In one embodiment, the aforementioned thickener may be one or more of the following: carboxymethyl cellulose, methyl cellulose, hydroxymethyl cellulose, ethyl cellulose, polyvinyl alcohol, oxidized starch, phosphorylated starch, casein, and salts thereof.
[0112] In one embodiment, the mass proportion of the thickener in the negative electrode slurry can be 0.1%-5%, for example, 0.1%, 0.2%, 0.5%, 0.6%, 1%, 2%, 3%, 4%, 5%, etc., preferably 0.5%-3%, and more preferably 0.6%-2%.
[0113] In one embodiment, the negative electrode active material layer includes a conductive material, so that the electrode has conductivity. The conductive material may include any conductive material as long as it does not cause chemical changes. Non-limiting examples of conductive materials include carbon-based materials (e.g., natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, etc.), metal-based materials (e.g., metal powder, metal fiber, etc., such as copper, nickel, aluminum, silver, etc.), conductive polymers (e.g., polyphenylene derivatives) and mixtures thereof.
[0114] In one embodiment, the negative electrode current collector may be selected from copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal, and combinations thereof.
[0115] Diaphragm:
[0116] In one embodiment, the lithium battery and electrochemical device of the present invention are provided with a separator between the positive electrode and the negative electrode to prevent short circuit. The material and shape of the separator used in the electrochemical device of the present invention are not particularly limited and can be any technology disclosed in the prior art.
[0117] In one embodiment, the separator includes a polymer or an inorganic substance formed of a material that is stable to the electrolyte of the present application.
[0118] In one embodiment, the separator may include a substrate layer and a surface treatment layer. The substrate layer is a non-woven fabric, a film or a composite film with a porous structure, and the material of the substrate layer is selected from at least one of polyethylene, polypropylene, polyethylene terephthalate and polyimide.
[0119] Electrolyte:
[0120] The lithium battery and electrochemical device of the present invention also include an electrolyte.
[0121] In one embodiment, the electrolyte includes a lithium salt and a solvent.
[0122] In one embodiment, the lithium salt includes at least one of an organic lithium salt or an inorganic lithium salt.
[0123] In one embodiment, the lithium salt includes, but is not limited to: lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium difluorophosphate (LiPO2F2), lithium bis(trifluoromethanesulfonyl)imide LiN(CF3SO2)2 (LiTFSI), lithium bis(fluorosulfonyl)imide Li(N(SO2F)2) (LiFSI), lithium bis(oxalatoborate) LiB(C2O4)2 (LiBOB) or lithium di(difluorooxalatoborate) LiBF2(C2O4) (LiDFOB).
[0124] In one embodiment, the solvent can be selected from one or more of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS) and diethyl sulfone (ESE).
[0125] In one embodiment, the electrolyte may further include additives, for example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high temperature performance, additives that improve battery low temperature performance, etc.
[0126] In some embodiments of the present invention, the aforementioned additives include 1,3-propane sultone, 1,4-butane sultone, propenyl-1,3-sultone, vinyl sulfate, 4-methyl vinyl sulfate, propenyl sulfate, saturated phosphate compounds and unsaturated phosphate compounds, tris (trimethylsilane) phosphate, tris (trimethylsilane) borate, tris (triethylsilane) borate, succinonitrile, glutaronitrile, ethylene glycol bis (propionitrile) ether, hexane trinitrile, adiponitrile, pimelonitrile, suberonitrile, azelaic acid dinitrile, sebaconitrile, and at least one of the following chemical formulas:
[0127]
[0128] Among them, R 41 , R 42 , R 43 Each independently selected from a C1-C5 saturated hydrocarbon group, an unsaturated hydrocarbon group, a halogenated hydrocarbon group, -Si(C m H 2m+1 )3, m is a natural number from 1 to 3, and R 41 , R 42 , R 43 At least one of them is an unsaturated hydrocarbon group.
[0129] Secondary battery:
[0130] In one embodiment, the secondary battery of the present invention includes the above-mentioned positive electrode sheet, negative electrode sheet, separator, electrolyte, etc., but is not limited thereto.
[0131] In one embodiment, the secondary battery according to the present invention is manufactured by stacking the above-mentioned positive and negative electrode sheets.
[0132] In one embodiment, the secondary battery of the present invention may include an outer package, which may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer package of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, such as one or more of polypropylene (PP), polybutylene terephthalate (PBT), polybutylene succinate (PBS), etc.
[0133] In one embodiment, the present invention further provides a battery module. The battery module includes the above-mentioned secondary battery. The battery module of the present invention may include multiple secondary batteries, and the specific number can be adjusted according to the application and capacity of the battery module.
[0134] In one embodiment, the present invention further provides a battery pack, which includes the above-mentioned battery module. The number of battery modules included in the battery pack can be adjusted according to the application and capacity of the battery pack.
[0135] The embodiments of the present invention will be described in more detail below through examples and comparative examples, wherein all examples and comparative examples are lithium ion battery sample groups prepared by the same process.
[0136] In order to intuitively and comprehensively reflect the advantages of the present invention, all embodiments and comparative examples record or perform the following tests: coating thickness record, discharge capacity test, capacity retention rate under 3C conditions, battery internal resistance test, 200 cycle battery capacity retention rate, and Mn dissolution content test.
[0137] It should be noted that the embodiments of the present invention are not limited to these examples.
[0138] Example 1
[0139] 1. Preparation of positive electrode active materials:
[0140] 1. The lithium source Li2CO3, the spherical manganese-containing precursor Mn3O4, H3BO3 and the metal oxides Al2O3 and Nb2O5 are mixed uniformly according to the stoichiometric ratio of n(Li):n(Mn):n(B):n(Al):n(Nb)=1:1.85:0.05:0.05:0.05 to form a first mixture, wherein the particle size D50 of the precursor Mn3O4 is 3.5 μm;
[0141] 2. calcining the first mixture in an air atmosphere at 750° C. for 16 hours to obtain a single-crystal lithium manganate material;
[0142] 3. Weigh the quasi-single-crystal lithium manganate material obtained in step 2, add the solvent anhydrous ethanol, stir evenly, add CeO2 material and fast ion conductor LiNbO3 to the above solution, continue stirring at 460°C for 6 hours to obtain a suspension mixed with the three, and dry for 12 hours. The dried powder is calcined at 550°C for 10 hours in an air atmosphere to obtain a quasi-single-crystal lithium manganate positive electrode active material compositely coated with CeO2 and LiNbO3. Record the coating layer thickness.
[0143] Among them, in the positive electrode active material, the mass proportion of CeO2 is 1%, and the mass proportion of fast ion conductor is 1%.
[0144] 2. Preparation of positive electrode sheet:
[0145] The positive electrode active material prepared in step 1, the conductive agent Super-P, and the binder PVDF were weighed and mixed evenly in a mass ratio of 95:3:2, mixed with the solvent NMR to obtain a positive electrode slurry, and evenly coated on an aluminum foil to form a positive electrode sheet.
[0146] 3. Preparation of negative electrode sheet:
[0147] The negative electrode active material graphite, conductive agent Super-P, binder CMC, and SBR were weighed and mixed evenly in a mass ratio of 95:3:1:1, mixed with solvent deionized water to obtain a negative electrode slurry, and evenly coated on a copper foil to form a negative electrode sheet.
[0148] 4. Preparation of batteries:
[0149] The positive electrode sheet prepared in step 2, the negative electrode sheet prepared in step 3 and the separator are assembled, and the electrolyte is injected to form a battery.
[0150] Example 2
[0151] 1. Preparation of positive electrode active materials:
[0152] 1. The lithium source Li2CO3, the spherical manganese-containing precursor Mn3O4, H3BO3 and the metal oxides Al2O3 and Nb2O5 are mixed uniformly according to the stoichiometric ratio of n(Li):n(Mn):n(B):n(Al):n(Nb)=1:1.85:0.05:0.05:0.05 to form a first mixture, wherein the particle size D50 of the precursor Mn3O4 is 3.5 μm;
[0153] 2. calcining the first mixture in an air atmosphere at 750° C. for 16 hours to obtain a single-crystal lithium manganate material;
[0154] 3. Weigh the quasi-single-crystal lithium manganate material obtained in step 2, add the solvent anhydrous ethanol, stir evenly, add CeO2 material and fast ion conductor LiNbO3 to the above solution, continue stirring at 460°C for 6 hours to obtain a suspension mixed with the three, and dry for 12 hours. The dried powder is calcined at 550°C for 10 hours in an air atmosphere to obtain a quasi-single-crystal lithium manganate positive electrode active material compositely coated with CeO2 and LiNbO3. Record the coating layer thickness.
[0155] Among them, in the positive electrode active material, the mass proportion of CeO2 is 1%, and the mass proportion of the fast ion conductor is 0.1%.
[0156] 2. Preparation of positive electrode sheet:
[0157] The positive electrode active material prepared in step 1, the conductive agent Super-P, and the binder PVDF were weighed and mixed evenly in a mass ratio of 95:3:2, mixed with the solvent NMR to obtain a positive electrode slurry, and evenly coated on an aluminum foil to form a positive electrode sheet.
[0158] 3. Preparation of negative electrode sheet:
[0159] The negative electrode active material graphite, conductive agent Super-P, binder CMC, and SBR were weighed and mixed evenly in a mass ratio of 95:3:1:1, mixed with solvent deionized water to obtain a negative electrode slurry, and evenly coated on a copper foil to form a negative electrode sheet.
[0160] 4. Preparation of batteries:
[0161] The positive electrode sheet prepared in step 2, the negative electrode sheet prepared in step 3 and the separator are assembled, and the electrolyte is injected to form a battery.
[0162] Example 3
[0163] 1. Preparation of positive electrode active materials:
[0164] 1. The lithium source Li2CO3, the spherical manganese-containing precursor Mn3O4, H3BO3 and the metal oxides Al2O3 and Nb2O5 are mixed uniformly according to the stoichiometric ratio of n(Li):n(Mn):n(B):n(Al):n(Nb)=1:1.85:0.05:0.05:0.05 to form a first mixture, wherein the particle size D50 of the precursor Mn3O4 is 3.5 μm;
[0165] 2. calcining the first mixture in an air atmosphere at 750° C. for 16 hours to obtain a single-crystal lithium manganate material;
[0166] 3. Weigh the quasi-single-crystal lithium manganate material obtained in step 2, add the solvent anhydrous ethanol, stir evenly, add CeO2 material and fast ion conductor LiNbO3 to the above solution, continue stirring at 460°C for 6 hours to obtain a suspension mixed with the three, and dry for 12 hours. The dried powder is calcined at 550°C for 10 hours in an air atmosphere to obtain a quasi-single-crystal lithium manganate positive electrode active material compositely coated with CeO2 and LiNbO3. Record the coating layer thickness.
[0167] Among them, in the positive electrode active material, the mass proportion of CeO2 is 1%, and the mass proportion of fast ion conductor is 2%.
[0168] 2. Preparation of positive electrode sheet:
[0169] The positive electrode active material prepared in step 1, the conductive agent Super-P, and the binder PVDF were weighed and mixed evenly in a mass ratio of 95:3:2, mixed with the solvent NMR to obtain a positive electrode slurry, and evenly coated on an aluminum foil to form a positive electrode sheet.
[0170] 3. Preparation of negative electrode sheet:
[0171] The negative electrode active material graphite, conductive agent Super-P, binder CMC, and SBR were weighed and mixed evenly in a mass ratio of 95:3:1:1, mixed with solvent deionized water to obtain a negative electrode slurry, and evenly coated on a copper foil to form a negative electrode sheet.
[0172] 4. Preparation of batteries:
[0173] The positive electrode sheet prepared in step 2, the negative electrode sheet prepared in step 3 and the separator are assembled, and the electrolyte is injected to form a battery.
[0174] Example 4
[0175] 1. Preparation of positive electrode active materials:
[0176] 1. The lithium source Li2CO3, the spherical manganese-containing precursor Mn3O4, H3BO3 and the metal oxides Al2O3 and Nb2O5 are mixed uniformly according to the stoichiometric ratio of n(Li):n(Mn):n(B):n(Al):n(Nb)=1:1.85:0.05:0.05:0.05 to form a first mixture, wherein the particle size D50 of the precursor Mn3O4 is 3.5 μm;
[0177] 2. calcining the first mixture in an air atmosphere at 750° C. for 16 hours to obtain a single-crystal lithium manganate material;
[0178] 3. Weigh the quasi-single-crystal lithium manganate material obtained in step 2, add the solvent anhydrous ethanol, stir evenly, add CeO2 material and fast ion conductor LiNbO3 to the above solution, continue stirring at 460°C for 6 hours to obtain a suspension mixed with the three, and dry for 12 hours. The dried powder is calcined at 550°C for 10 hours in an air atmosphere to obtain a quasi-single-crystal lithium manganate positive electrode active material compositely coated with CeO2 and LiNbO3. Record the coating layer thickness.
[0179] Among them, in the positive electrode active material, the mass proportion of CeO2 is 0.1%, and the mass proportion of the fast ion conductor is 1%.
[0180] 2. Preparation of positive electrode sheet:
[0181] The positive electrode active material prepared in step 1, the conductive agent Super-P, and the binder PVDF were weighed and mixed evenly in a mass ratio of 95:3:2, mixed with the solvent NMR to obtain a positive electrode slurry, and evenly coated on an aluminum foil to form a positive electrode sheet.
[0182] 3. Preparation of negative electrode sheet:
[0183] The negative electrode active material graphite, conductive agent Super-P, binder CMC, and SBR were weighed and mixed evenly in a mass ratio of 95:3:1:1, mixed with solvent deionized water to obtain a negative electrode slurry, and evenly coated on a copper foil to form a negative electrode sheet.
[0184] 4. Preparation of batteries:
[0185] The positive electrode sheet prepared in step 2, the negative electrode sheet prepared in step 3 and the separator are assembled, and the electrolyte is injected to form a battery.
[0186] Example 5
[0187] 1. Preparation of positive electrode active materials:
[0188] 1. The lithium source Li2CO3, the spherical manganese-containing precursor Mn3O4, H3BO3 and the metal oxides Al2O3 and Nb2O5 are mixed uniformly according to the stoichiometric ratio of n(Li):n(Mn):n(B):n(Al):n(Nb)=1:1.85:0.05:0.05:0.05 to form a first mixture, wherein the particle size D50 of the precursor Mn3O4 is 3.5 μm;
[0189] 2. calcining the first mixture in an air atmosphere at 750° C. for 16 hours to obtain a single-crystal lithium manganate material;
[0190] 3. Weigh the quasi-single-crystal lithium manganate material obtained in step 2, add the solvent anhydrous ethanol, stir evenly, add CeO2 material and fast ion conductor LiNbO3 to the above solution, continue stirring at 460°C for 6 hours to obtain a suspension mixed with the three, and dry for 12 hours. The dried powder is calcined at 550°C for 10 hours in an air atmosphere to obtain a quasi-single-crystal lithium manganate positive electrode active material compositely coated with CeO2 and LiNbO3. Record the coating layer thickness.
[0191] Among them, in the positive electrode active material, the mass proportion of CeO2 is 2%, and the mass proportion of fast ion conductor is 1%.
[0192] 2. Preparation of positive electrode sheet:
[0193] The positive electrode active material prepared in step 1, the conductive agent Super-P, and the binder PVDF were weighed and mixed evenly in a mass ratio of 95:3:2, mixed with the solvent NMR to obtain a positive electrode slurry, and evenly coated on an aluminum foil to form a positive electrode sheet.
[0194] 3. Preparation of negative electrode sheet:
[0195] The negative electrode active material graphite, conductive agent Super-P, binder CMC, and SBR were weighed and mixed evenly in a mass ratio of 95:3:1:1, mixed with solvent deionized water to obtain a negative electrode slurry, and evenly coated on a copper foil to form a negative electrode sheet.
[0196] 4. Preparation of batteries:
[0197] The positive electrode sheet prepared in step 2, the negative electrode sheet prepared in step 3 and the separator are assembled, and the electrolyte is injected to form a battery.
[0198] Example 6
[0199] 1. Preparation of positive electrode active materials:
[0200] 1. The lithium source Li2CO3, the spherical manganese-containing precursor Mn3O4, H3BO3 and the metal oxides Al2O3 and Nb2O5 are mixed uniformly according to the stoichiometric ratio of n(Li):n(Mn):n(B):n(Al):n(Nb)=1:1.85:0.05:0.05:0.05 to form a first mixture, wherein the particle size D50 of the precursor Mn3O4 is 3.5 μm;
[0201] 2. calcining the first mixture in an air atmosphere at 750° C. for 16 hours to obtain a single-crystal lithium manganate material;
[0202] 3. Weigh the quasi-single-crystal lithium manganate material obtained in step 2, add the solvent anhydrous ethanol, stir evenly, add CeO2 material and fast ion conductor LiNbO3 to the above solution, continue stirring at 460°C for 6 hours to obtain a suspension mixed with the three, and dry for 12 hours. The dried powder is calcined at 550°C for 10 hours in an air atmosphere to obtain a quasi-single-crystal lithium manganate positive electrode active material compositely coated with CeO2 and LiNbO3. Record the coating layer thickness.
[0203] Among them, in the positive electrode active material, the mass proportion of CeO2 is 0.5%, and the mass proportion of fast ion conductor is 2.5%.
[0204] 2. Preparation of positive electrode sheet:
[0205] The positive electrode active material prepared in step 1, the conductive agent Super-P, and the binder PVDF were weighed and mixed evenly in a mass ratio of 95:3:2, mixed with the solvent NMR to obtain a positive electrode slurry, and evenly coated on an aluminum foil to form a positive electrode sheet.
[0206] 3. Preparation of negative electrode sheet:
[0207] The negative electrode active material graphite, conductive agent Super-P, binder CMC, and SBR were weighed and mixed evenly in a mass ratio of 95:3:1:1, mixed with solvent deionized water to obtain a negative electrode slurry, and evenly coated on a copper foil to form a negative electrode sheet.
[0208] 4. Preparation of batteries:
[0209] The positive electrode sheet prepared in step 2, the negative electrode sheet prepared in step 3 and the separator are assembled, and the electrolyte is injected to form a battery.
[0210] Example 7
[0211] 1. Preparation of positive electrode active materials:
[0212] 1. The lithium source Li2CO3, the spherical manganese-containing precursor Mn3O4, H3BO3 and the metal oxides Al2O3 and Nb2O5 are mixed uniformly according to the stoichiometric ratio of n(Li):n(Mn):n(B):n(Al):n(Nb)=1:1.85:0.05:0.05:0.05 to form a first mixture, wherein the particle size D50 of the precursor Mn3O4 is 3.5 μm;
[0213] 2. calcining the first mixture in an air atmosphere at 750° C. for 16 hours to obtain a single-crystal lithium manganate material;
[0214] 3. Weigh the quasi-single-crystal lithium manganate material obtained in step 2, add the solvent anhydrous ethanol, stir evenly, add CeO2 material and fast ion conductor Li2TiO3 to the above solution, continue stirring at 460°C for 6 hours to obtain a suspension of the three mixtures, and dry for 12 hours. The dried powder is calcined at 550°C for 10 hours in an air atmosphere to obtain a quasi-single-crystal lithium manganate positive electrode active material compositely coated with CeO2 and Li2TiO3. Record the coating layer thickness.
[0215] Among them, in the positive electrode active material, the mass proportion of CeO2 is 1%, and the mass proportion of fast ion conductor Li2TiO3 is 1%.
[0216] 2. Preparation of positive electrode sheet:
[0217] The positive electrode active material prepared in step 1, the conductive agent Super-P, and the binder PVDF were weighed and mixed evenly in a mass ratio of 95:3:2, mixed with the solvent NMR to obtain a positive electrode slurry, and evenly coated on an aluminum foil to form a positive electrode sheet.
[0218] 3. Preparation of negative electrode sheet:
[0219] The negative electrode active material graphite, conductive agent Super-P, binder CMC, and SBR were weighed and mixed evenly in a mass ratio of 95:3:1:1, mixed with solvent deionized water to obtain a negative electrode slurry, and evenly coated on a copper foil to form a negative electrode sheet.
[0220] 4. Preparation of batteries:
[0221] The positive electrode sheet prepared in step 2, the negative electrode sheet prepared in step 3 and the separator are assembled, and the electrolyte is injected to form a battery.
[0222] Example 8
[0223] 1. Preparation of positive electrode active materials:
[0224] 1. Lithium source Li2CO3, spherical manganese-containing precursor Mn3O4, H3BO3 and metal oxides Al2O3, Nb2O 5、 CoO is mixed evenly according to the stoichiometric ratio of n(Li):n(Mn):n(B):n(Al):n(Nb):n(Co)=1:1.85:0.05:0.05:0.02:0.03 to form a first mixture, and the particle size D50 of the precursor Mn3O4 is 3.5 μm;
[0225] 2. calcining the first mixture in an air atmosphere at 750° C. for 16 hours to obtain a single-crystal lithium manganate material;
[0226] 3. Weigh the quasi-single-crystal lithium manganate material obtained in step 2, add the solvent anhydrous ethanol, stir evenly, add CeO2 material and fast ion conductor LiNbO3 to the above solution, continue stirring at 460°C for 6 hours to obtain a suspension mixed with the three, and dry for 12 hours. The dried powder is calcined at 550°C for 10 hours in an air atmosphere to obtain a quasi-single-crystal lithium manganate positive electrode active material compositely coated with CeO2 and LiNbO3. Record the coating layer thickness.
[0227] Among them, in the positive electrode active material, the mass proportion of CeO2 is 0.5%, and the mass proportion of fast ion conductor is 2.5%.
[0228] 2. Preparation of positive electrode sheet:
[0229] The positive electrode active material prepared in step 1, the conductive agent Super-P, and the binder PVDF were weighed and mixed evenly in a mass ratio of 95:3:2, mixed with the solvent NMR to obtain a positive electrode slurry, and evenly coated on an aluminum foil to form a positive electrode sheet.
[0230] 3. Preparation of negative electrode sheet:
[0231] The negative electrode active material graphite, conductive agent Super-P, binder CMC, and SBR were weighed and mixed evenly in a mass ratio of 95:3:1:1, mixed with solvent deionized water to obtain a negative electrode slurry, and evenly coated on a copper foil to form a negative electrode sheet.
[0232] 4. Preparation of batteries:
[0233] The positive electrode sheet prepared in step 2, the negative electrode sheet prepared in step 3 and the separator are assembled, and the electrolyte is injected to form a battery.
[0234] Comparative Example 1
[0235] 1. Preparation of positive electrode active materials:
[0236] 1. The lithium source Li2CO3, the spherical manganese-containing precursor Mn3O4, H3BO3 and the metal oxides Al2O3 and Nb2O5 are mixed uniformly according to the stoichiometric ratio of n(Li):n(Mn):n(B):n(Al):n(Nb)=1:1.85:0.05:0.05:0.05 to form a first mixture, wherein the particle size D50 of the precursor Mn3O4 is 3.5 μm;
[0237] 2. The first mixture was calcined in an air atmosphere at 750° C. for 16 hours to obtain a single-crystal lithium manganate positive electrode active material.
[0238] 2. Preparation of positive electrode sheet:
[0239] The positive electrode active material prepared in step 1, the conductive agent Super-P, and the binder PVDF were weighed and mixed evenly in a mass ratio of 95:3:2, mixed with the solvent NMR to obtain a positive electrode slurry, and evenly coated on an aluminum foil to form a positive electrode sheet.
[0240] 3. Preparation of negative electrode sheet:
[0241] The negative electrode active material graphite, conductive agent Super-P, binder CMC, and SBR were weighed and mixed evenly in a mass ratio of 95:3:1:1, mixed with solvent deionized water to obtain a negative electrode slurry, and evenly coated on a copper foil to form a negative electrode sheet.
[0242] 4. Preparation of batteries:
[0243] The positive electrode sheet prepared in step 2, the negative electrode sheet prepared in step 3 and the separator are assembled, and the electrolyte is injected to form a battery.
[0244] Comparative Example 2
[0245] 1. Preparation of positive electrode active materials:
[0246] 1. The lithium source Li2CO3, the spherical manganese-containing precursor Mn3O4, H3BO3 and the metal oxides Al2O3 and Nb2O5 are mixed uniformly according to the stoichiometric ratio of n(Li):n(Mn):n(B):n(Al):n(Nb)=1:1.85:0.05:0.05:0.05 to form a first mixture, wherein the particle size D50 of the precursor Mn3O4 is 3.5 μm;
[0247] 2. calcining the first mixture in an air atmosphere at 750° C. for 16 hours to obtain a single-crystal lithium manganate material;
[0248] 3. Weigh the quasi-single-crystal lithium manganate material obtained in step 2, add the solvent anhydrous ethanol, stir evenly, add the fast ion conductor LiNbO3 to the above solution, continue stirring at 460°C for 6 hours to obtain a suspension of the three mixtures, and dry for 12 hours. The dried powder is calcined at 550°C for 10 hours in an air atmosphere to obtain a quasi-single-crystal lithium manganate positive electrode active material coated with LiNbO3. Record the coating layer thickness.
[0249] Among them, the mass of fast ion conductors accounts for 1% of the positive electrode active materials.
[0250] 2. Preparation of positive electrode sheet:
[0251] The positive electrode active material prepared in step 1, the conductive agent Super-P, and the binder PVDF were weighed and mixed evenly in a mass ratio of 95:3:2, mixed with the solvent NMR to obtain a positive electrode slurry, and evenly coated on an aluminum foil to form a positive electrode sheet.
[0252] 3. Preparation of negative electrode sheet:
[0253] The negative electrode active material graphite, conductive agent Super-P, binder CMC, and SBR were weighed and mixed evenly in a mass ratio of 95:3:1:1, mixed with solvent deionized water to obtain a negative electrode slurry, and evenly coated on a copper foil to form a negative electrode sheet.
[0254] 4. Preparation of batteries:
[0255] The positive electrode sheet prepared in step 2, the negative electrode sheet prepared in step 3 and the separator are assembled, and the electrolyte is injected to form a battery.
[0256] Comparative Example 3
[0257] 1. Preparation of positive electrode active materials:
[0258] 1. The lithium source Li2CO3, the spherical manganese-containing precursor Mn3O4, H3BO3 and the metal oxides Al2O3 and Nb2O5 are mixed uniformly according to the stoichiometric ratio of n(Li):n(Mn):n(B):n(Al):n(Nb)=1:1.85:0.05:0.05:0.05 to form a first mixture, wherein the particle size D50 of the precursor Mn3O4 is 3.5 μm;
[0259] 2. calcining the first mixture in an air atmosphere at 750° C. for 16 hours to obtain a single-crystal lithium manganate material;
[0260] 3. Weigh the quasi-single-crystal lithium manganate material obtained in step 2, add the solvent anhydrous ethanol, stir evenly, add the CeO2 material to the above solution, continue stirring at 460°C for 6 hours to obtain a suspension of the three mixtures, and dry for 12 hours. The dried powder is calcined at 550°C for 10 hours in an air atmosphere to obtain a CeO2-coated quasi-single-crystal lithium manganate positive electrode active material. Record the coating layer thickness.
[0261] Among them, the mass proportion of CeO2 in the positive electrode active material is 1%.
[0262] 2. Preparation of positive electrode sheet:
[0263] The positive electrode active material prepared in step 1, the conductive agent Super-P, and the binder PVDF were weighed and mixed evenly in a mass ratio of 95:3:2, mixed with the solvent NMR to obtain a positive electrode slurry, and evenly coated on an aluminum foil to form a positive electrode sheet.
[0264] 3. Preparation of negative electrode sheet:
[0265] The negative electrode active material graphite, conductive agent Super-P, binder CMC, and SBR were weighed and mixed evenly in a mass ratio of 95:3:1:1, mixed with solvent deionized water to obtain a negative electrode slurry, and evenly coated on a copper foil to form a negative electrode sheet.
[0266] 4. Preparation of batteries:
[0267] The positive electrode sheet prepared in step 2, the negative electrode sheet prepared in step 3 and the separator are assembled, and the electrolyte is injected to form a battery.
[0268] Comparative Example 4
[0269] 1. Preparation of positive electrode active materials:
[0270] 1. The lithium source Li2CO3, the spherical manganese-containing precursor Mn3O4 and H3BO3 are mixed uniformly according to the stoichiometric ratio of 1:1.85:0.05 to form a first mixture, wherein the particle size D50 of the precursor Mn3O4 is 3.5 μm;
[0271] 2. The first mixture was calcined in an air atmosphere at 750° C. for 16 hours to obtain a single-crystal lithium manganate positive electrode active material.
[0272] 2. Preparation of positive electrode sheet:
[0273] The positive electrode active material prepared in step 1, the conductive agent Super-P, and the binder PVDF were weighed and mixed evenly in a mass ratio of 95:3:2, mixed with the solvent NMR to obtain a positive electrode slurry, and evenly coated on an aluminum foil to form a positive electrode sheet.
[0274] 3. Preparation of negative electrode sheet:
[0275] The negative electrode active material graphite, conductive agent Super-P, binder CMC, and SBR were weighed and mixed evenly in a mass ratio of 95:3:1:1, mixed with solvent deionized water to obtain a negative electrode slurry, and evenly coated on a copper foil to form a negative electrode sheet.
[0276] 4. Preparation of batteries:
[0277] The positive electrode sheet prepared in step 2, the negative electrode sheet prepared in step 3 and the separator are assembled, and the electrolyte is injected to form a battery.
[0278] The batteries prepared in Examples 1-8 and Comparative Examples 1-4 were tested as follows.
[0279] First discharge capacity test:
[0280] The battery was discharged at a constant current of 0.1C to a cut-off voltage of 3.0V.
[0281] Rate performance test:
[0282] At room temperature (25°C), the fully charged battery is discharged at a current of 0.1C to a cut-off voltage of 3.0V. The capacity obtained by the test is C0.
[0283] At room temperature (25°C), a fully charged battery is discharged at a current of 3C to a cut-off voltage of 3.0V. The capacity obtained by the test is C1, and C1 / C0 is the 3C discharge capacity retention rate below.
[0284] Battery internal resistance test:
[0285] Obtained through DCR test, 25℃, 3C discharge for 10 seconds.
[0286] Cyclic battery capacity retention rate:
[0287] At a temperature of 45°C, charge at a current of 0.2C to a charging cut-off voltage of 4.2V, switch to constant voltage charging to a cut-off current of 0.05C, let stand for 0.5h, then discharge at a current of 0.2C to a cut-off voltage of 3.0V, let stand for 0.5h, enter the next charge and discharge cycle, and so on, for a total of 200 charge and discharge cycles.
[0288] Mn dissolution content test:
[0289] Weigh about 0.1g of negative electrode powder (accurate to ±0.0003g) of two portions of each embodiment, place in a 100ml beaker, add a small amount of distilled water to wet the bottom of the cup, then add 5ml12mol / L HCl (made in Shandong, GR) to dissolve, heat on an electric heating plate for 20min, remove and cool, dilute and test. Introduce the prepared series of standard solutions into an iCAP7000 inductively coupled plasma spectrometer (ICP) (made in the United States), and measure the intensity of manganese in the standard solution at the wavelength of the element manganese to be measured. When the linear correlation coefficient of the working curve r≥0.9995, the measurement can be performed.
[0290] The results are shown in the following table.
[0291]
[0292]
[0293] According to the above table, it can be seen that: comparing Example 1 with Comparative Examples 1 to 3, the present application comprises CeO2 and a fast ion conductor coated on the surface of the quasi-single-crystalline lithium manganese oxide, and the synergistic effect of CeO2 and the fast ion conductor can, on the one hand, effectively isolate the contact between the electrolyte and the lithium manganese oxide material, reduce the dissolution of divalent manganese ions, and effectively prevent the damage of the quasi-single-crystalline lithium manganese oxide material to the rolling, thereby improving the cycle performance of the battery; on the other hand, the positive electrode active material of the present application has good lithium ion transport performance, and the rate performance of the battery is optimized. Using CeO2 and a fast ion conductor as the coating layer material is conducive to preparing a thin coating layer and improving the internal resistance of the battery.
[0294] Comparing Example 1 with Comparative Example 4, in Example 1, by doping and coating the single-crystal lithium manganese oxide material, the cycle performance and rate performance of the battery are improved, indicating that doping and coating the single-crystal lithium manganese oxide material at the same time is beneficial to the improvement of the electrochemical performance of the battery.
[0295] It should be pointed out that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A positive electrode active material, characterized in that It includes a quasi-single-crystal lithium manganate material and a coating layer formed on the surface of the quasi-single-crystal lithium manganate material; The coating layer includes CeO2 and a fast ion conductor; The general formula of the single-crystal lithium manganate material is Li 1+a Mn 2-a-b-c B b M c O4; Among them, 0.001≤a≤0.30, 0.001≤b≤0.2, 0.001≤c≤0.2; M is a metal element.
2. The positive electrode active material according to claim 1, characterized in that The fast ion conductor includes LiNbO3, Li4Ti5O 12 , at least one of Li2TiO3, LiAlO2, LiTaO3, LiMoO3, Li2RuO3 or Li2WO4.
3. The positive electrode active material according to claim 1, characterized in that The M includes at least two of Mg, Al, Ca, Ti, Cu, Zn, Y, Zr, Nb, Mo, Ru, Sn, and Sb.
4. The positive electrode active material according to claim 3, characterized in that The M includes at least two of Al, Mg, Ti, Co, and Nb.
5. The positive electrode active material according to claim 1, characterized in that The coating layer has a thickness of 10 to 50 nm.
6. The positive electrode active material according to claim 1, characterized in that Based on the mass of the positive electrode active material being 100%, the mass of the fast ion conductor material accounts for 0.1% to 2%; and / or, Taking the mass of the positive electrode active material as 100%, the mass of CeO2 accounts for 0.1% to 2%.
7. A method for preparing a positive electrode active material, characterized in that: The steps include: S1, uniformly mixing a spherical or quasi-spherical Mn-containing precursor, a lithium source, a B source and an M source to form a first mixture; S2, calcining the first mixture in an air atmosphere to obtain a single-crystal lithium manganate material; S3, weighing the quasi-single-crystal lithium manganate material obtained in step S2, adding a solvent, and stirring evenly to form a first solution; S4, adding CeO2 material and fast ion conductor material to the first solution prepared in step S3, and continuing to stir until a suspension is formed; S5, dry; S6, calcining the dried powder obtained in step S5 under air atmosphere to obtain a positive electrode active material; Wherein, the particle size of the Mn-containing precursor is 1 μm to 5 μm; In the step S2, the calcination temperature is 600°C to 880°C.
8. The method according to claim 7, characterized in that The Mn-containing precursor includes one or two of manganese tetraoxide, manganese trioxide, and manganese carbonate; and / or, The lithium source is one or both of lithium carbonate and lithium hydroxide; and / or, The M source is an oxide or sulfate of the metal element M.
9. A positive electrode sheet comprising the positive electrode active material according to any one of claims 1 to 4, a conductive agent and a binder.
10. A battery comprising the positive electrode sheet, the negative electrode sheet, the separator and the electrolyte according to claim 9.
Citation Information
Patent Citations
Single-crystal lithium nickel manganese cobalt positive electrode material, preparation method thereof and lithium ion battery
CN106505193A
Single-crystal positive electrode material, preparation method thereof and lithium ion battery
CN117199325A
Positive active material and preparation method thereof, positive pole piece, secondary battery, battery module, battery pack and electric device
CN118613932A
Multifunctional-layer lithium manganate positive electrode material, preparation method thereof, positive electrode plate and battery
CN119008931A
Lithium cobalt oxide positive electrode material and preparation method therefor
WO2024145997A1